Script Usage in Standardized and Customized Service Encounters: Implications for Perceived Service Quality - Victorino, Liana; Verma, Rohit; Wardell, Don G. (Production and Operations Management, 2013)
This study examines the effect that verbal scripts have on customer perceived service quality for two distinct service process types. We designed a video experiment that varied the level of verbal scripting for standardized and customized service encounters. We found that in standardized service encounters, an increase in the level of verbal scripting had no effect on perceived service quality. However, for customized encounters, perceived service quality was impacted. More specifically, a predominantly scripted encounter for customized service processes, on average, resulted in the lowest perception of service quality by respondents. Since verbal scripting was shown to impact customer perceptions of service quality, we suggest that a service provider's decision regarding the degree of verbal scripting is an important service design consideration.